Jaringan Syaraf Tiruan Pengaruh Infuse Pada Berat Badan Pria dengan Menggunakan Metode Backpropagation - Nurina Sianturi (Journal of Computer System and Informatics (JoSYC), 2020)
Artificial Neural Network or in short ANN, is a computational system where architecture and operations are inspired by knowledge of biological nerve cells in the brain, which is one of the artificial representations of the human brain that always tries to stimulate the learning process in the human brain. Infusion or also called intravenous infusion is a fluid that works to increase body fluids. Infusion fluid also functions to maintain normal body functions and provide adequate calorie intake, especially for male patients who are recovering and after surgery. In this study, implementing a backpropagation neural network method to study existing data in order to prove the presence or absence of the influence of the infusion on male body weight. The input used is an effect that occurs after the use of infusion, then represented by using the backpropagation algorithm